iTRAQ-BASED Proteomic Analysis of the Mechanism of Fructose on Improving Fengycin Biosynthesis in Bacillus Amyloliquefaciens - Hedong Lu; Ruili Li; Panping Yang; Weibo Luo; Shunxian Chen; Muhammad Bilal; Hai Xu; Chengyuan Gu; Shuai Liu; Yuping Zhao; Chengxin Geng; Li Zhao (Molecules, 2021)
Fengycin, as a lipopeptide produced by Bacillus subtilis, displays potent activity against filamentous fungi, including Aspergillus flavus and Soft-rot fungus, which exhibits a wide range of potential applications in food industries, agriculture, and medicine. To better clarify the regulatory mechanism of fructose on fengycin biosynthesis, the iTRAQ-based proteomic analysis was utilized to investigate the differentially expressed proteins of B. amyloliquefaciens fmb-60 cultivated in ML (without fructose) and MLF (with fructose) medium. The results indicated that a total of 811 proteins, including 248 proteins with differential expression levels (162 which were upregulated (fold > 2) and 86, which were downregulated (fold < 0.5) were detected, and most of the proteins are associated with cellular metabolism, biosynthesis, and biological regulation process. Moreover, the target genes’ relative expression was conducted using quantitative real-time PCR to validate the proteomic analysis results. Based on the results of proteome analysis, the supposed pathways of fructose enhancing fengycin biosynthesis in B. amyloliquefaciens fmb-60 can be summarized as improvement of the metabolic process, including cellular amino acid and amide, fatty acid biosynthesis, peptide and protein, nucleotide and nucleobase-containing compound, drug/toxin, cofactor, and vitamin; reinforcement of peptide/protein translation, modification, biological process, and response to a stimulus. In conclusion, this study represents a comprehensive and systematic investigation of the fructose mechanism on improving fengycin biosynthesis in B. amyloliquefaciens, which will provide a road map to facilitate the potential application of fengycin or its homolog in defending against filamentous fungi.